Effect of the water and oleogelator content on characteristics and stability of BC-loaded oleogel-based emulsion. (15th September 2022) - Yang, Shu; Saleh, Ahmed S.M.; Yang, Qiang; Cui, Xiaotong; Duan, Yumin; Xiao, Zhigang
Abstract: Oleogel samples were prepared from sunflower oil with β-Sitosterol (Sit) and Stearic acid (SA) mixture. Water was added to prepare an oleogel-based emulsion. The oleogel-based emulsion showed a white and smooth appearance without separation after storage at 5 ο C for 24 h. The firmness of emulsion reduced as the water content increased, while it was increased as the oleogelator concentration increased. Additionally, diffraction patterns and thermal properties of emulsion varied depending on water content. Furthermore, all the oleogel-based emulsion samples showed a positive slope of storage modulus (G′) and loss modulus (G″) with the increase in frequency. On the other hand, the stability of β-carotene (BC) -loaded emulsion to different conditions was evaluated. A greater BC content was found for samples stored in the dark and under natural light than that of samples stored under UV light. Oleogel and oleogel-based emulsion showed a good BC release rate in simulated gastrointestinal fluids. The obtained results indicate that functional BC-fortified emulsion can be successfully prepared using β-Sitosterol and Stearic acid mixture with sunflower oil and water. Highlights: Functional emulsion was prepared from β-sitosterol-stearic acid-based oleogel. Microstructures of emulsion varied depending on the water and oleogelator content. β-carotene loaded emulsion exhibited good stability under different conditions. Oleogel and oleogel-based emulsion showed a good BC release rate.